India's Development and Economic Aid Embassy of the United States of America - Planning Commission (Planning Commission, 1964)
India has had an impressive record of economic development since achieving independence in 1947. Despite some problems, the country has probably accomplished more in these 18 years than in any previous century. While foreign assistance has played an important role, India itself has supplied So percent of its own development requirements. India today manufactures equipment ranging from aircraft to transistors. Many Indian industries which formerly depended mainly on imported components now arc nearing self-sufficiency. The automobile industry, for example, today makes nearly 85 per cent of the components used in Indian-produced cars and trucks.
Embassy of the United States of America
Embassy of the United States of America